Why do Argos satellite tags stop relaying data?. Issue 11 (1st May 2021) - Hays, Graeme C.; Laloë, Jacques‐Olivier; Rattray, Alex; Esteban, Nicole
Abstract: Satellite tracking of animals is very widespread across a range of marine, freshwater, and terrestrial taxa. Despite the high cost of tags and the advantages of long deployments, the reasons why tracking data from tags stop being received are rarely considered, but possibilities include shedding of the tag, damage to the tag (e.g., the aerial), biofouling, battery exhaustion, or animal mortality. We show how information relayed via satellite tags can be used to assess why tracking data stop being received. As a case study to illustrate general approaches that are broadly applicable across taxa, we examined data from Fastloc‐GPS Argos tags deployed between 2012 and 2019 on 78 sea turtles of two species, the green turtle ( Chelonia mydas ) and the hawksbill turtle ( Eretmochelys imbricata ). Tags transmitted for a mean of 267 days ( SD = 113 days, range: 26–687 days, median = 251 days). In 68 of 78 (87%) cases, battery failure was implicated as the reason why tracking data stopped being received. Some biofouling of the saltwater switches, which synchronize transmissions with surfacing, was evident in a few tags but never appeared to be the reason that data reception ceased. Objectively assessing why tags fail will direct improvements to tag design, setup, and deployment regardless of the study taxa. Assessing why satellite tags stop transmitting will also inform on the fate of tagged animals, for example, whether they are alive or dead at the end of the study, which may allow improved estimates of survival rates. Abstract : We show how information relayed via satellite tags can be used to assess why tracking data stop being received. Assessing why satellite tags stop transmitting will inform on the fate of tagged animals, for example, whether they are alive or dead at the end of the study, thereby allowing improved estimates of survival rates and areas where animals may be experiencing high mortality. Furthermore, objectively assessing why tags fail will direct improvements to tag design, setup, and deployment regardless of the study taxa.